Półka literacka 2019 - Nęcka, Agnieszka (Postscriptum Polonistyczne, 2020)
The essay presents an overview of the most important and most interesting prose and poetry publications that appeared on the Polish publishing market in 2019. The past year belonged mainly to artists perfectly rooted in the readers’ awareness. Particularly appreciated were especially works with underlying autobiographical themes, revisiting the often difficult past to try to sort out the “here and now”, socially engaged books, and books that remind us about shortcomings of the communication code. The authors of the recommended books included: Justyna Bargielska, Konrad Góra, Ewa Kuryluk, Mikołaj Łoziński, Krystyna Miłobędzka, Wojciech Nowicki, Jakub Pszoniak, Dominika Słowik, and Paweł Sołtys.